Fabrication, Optimization, and Evaluation of Rotigotine-Loaded Chitosan Nanoparticles for Nose-To-Brain Delivery - Angeline Shak. Tzeyung; Shadab Md; Subrat Kumar Bhattamisra; Thiagarajan Madheswaran; Nabil A. Alhakamy; Hibah M. Aldawsari; Ammu K. Radhakrishnan (Pharmaceutics, 2019)
The objective of the present study was to develop, optimize, and evaluate rotigotine-loaded chitosan nanoparticles (RNPs) for nose-to-brain delivery. Rotigotine-loaded chitosan nanoparticles were prepared by the ionic gelation method and optimized for various parameters such as the effect of chitosan, sodium tripolyphosphate, rotigotine concentration on particle size, polydispersity index (PDI), zeta potential, and entrapment efficiency. The prepared nanoparticles were characterized using photon correlation spectroscopy, transmission electron microscopy, scanning electron microscopy, atomic force microscopy, fourier-transform infrared spectroscopy, and X-ray diffraction. The developed RNPs showed a small hydrodynamic particle size (75.37 ± 3.37 nm), small PDI (0.368 ± 0.02), satisfactory zeta potential (25.53 ± 0.45 mV), and very high entrapment efficiency (96.08 ± 0.01). The 24-h in vitro release and ex vivo nasal permeation of rotigotine from the nanoparticles were 49.45 ± 2.09% and 92.15 ± 4.74% while rotigotine solution showed corresponding values of 95.96 ± 1.79%and 58.22 ± 1.75%, respectively. The overall improvement ratio for flux and permeability coefficient were found to be 4.88 and 2.67 when compared with rotigotine solution. A histopathological study showed that the nanoparticulate formulation produced no toxicity or structural damage to nasal mucosa. Our results indicated that rotigotine-loaded chitosan nanoparticles provide an efficient carrier for nose-to-brain delivery.